2013
DOI: 10.1111/faf.12051
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and monitoring compliance in no‐take marine reserves

Abstract: No‐take marine reserves are increasingly popular tools for conservation and fisheries management. While much attention has been paid to evaluating the effects of design aspects (size, location, etc.) in achieving reserve objectives, less emphasis has been placed on the role of stakeholder compliance. Therefore, the first aim of this study was to evaluate the state of compliance literature and examine the methods used to measure compliance in reserves. The state of compliance literature is limited, although pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
108
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 116 publications
(294 reference statements)
0
108
0
Order By: Relevance
“…The mere presence of an MPA does not guarantee fishers' compliance, and its effectiveness can be eroded by illegal fishing. Indeed, ecological performance of MPAs has been clearly linked to compliance (Pollnac et al 2010, Bergseth et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The mere presence of an MPA does not guarantee fishers' compliance, and its effectiveness can be eroded by illegal fishing. Indeed, ecological performance of MPAs has been clearly linked to compliance (Pollnac et al 2010, Bergseth et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, customary knowledge was based on direct observations of resources and natural cycles, which have been shown to result in adaptive management, (Berkes et al 2000, Wilson et al 2006, Mahon et al 2008, in other words, "learning by doing" (Walters and Holling 1990). Furthermore, incorporating fishers into the monitoring and management process encourages responsibility for the resources and develops community-based values for acceptable harvest practices that are enforced and regulated by users themselves (Prince 2003, Wiber et al 2004, Cinner et al 2009, Basurto and Ostrom 2009, Bergseth et al 2015.…”
Section: Developing Local Capacity For Stewardshipmentioning
confidence: 99%
“…The effectiveness of marine reserves and marine protected areas (MPAs) depends on reducing or eliminating fishing pressure within their boundaries (Ainsworth et al 2012;Gaines et al 2010;Kritzer 2004;Sethi and Hilborn 2008). Reserves with high rates of noncompliance show limited recovery of fish communities (Ainsworth et al 2012;Campbell et al 2012;Kritzer 2004;McClanahan et al 2009), and compliance information can predict the recovery of fish biomass without incorporating any reserve design factors (Bergseth et al 2015). Furthermore, a global study of marine reserves identified enforcement as one of five key features that influenced effectiveness (Edgar et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, compliance levels reported by resource users and population density were the best predictors of reserve effectiveness in a study of 56 tropical marine reserves (Pollnac et al 2010). However, despite their importance for recovery, compliance rates are rarely quantified (Sethi and Hilborn 2008;Smallwood and Beckley 2012), and when compliance is measured, most data are qualitative (anecdotal or expert opinion) and direct empirical observations are rare (Bergseth et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation